OPTIMASI PROSES PEMBUATAN TEPUNG KACANG SACHA INCHI (Plukenetia volubilis L.) MENGGUNAKAN RESPONSE SURFACE METHOD - Yelliantty, Yelliantty; Limbong, Son Junifer (Pasundan Food Technology Journal (PFTJ), 2025)
This research aims to obtain the optimal process in the production of inchi sacha bean flour using Design-Expert 13 Response Surface Method based on chemical and physical properties. The benefit of this research is to provide information on the use of inchi sacha beans as functional food flour. The research consisted of two stages, namely preliminary research and main research. The preliminary research was to analyze the fat in sacha inchi beans, while the main research conducted was to determine the process optimization of sacha inchi bean flour using the Design Expert 13 program using the Response Surface Method by analyzing each process recommended by the program. The analysis conducted is testing water content, analyzing fat content and solubility. The research results based on the prediction of Design Expert 13 obtained as many as 13 recommended runs. There was one optimal run process with a desirability value of 0.949 with a drying temperature of 80°C and a drying time of 5.325 hours. Based on the selected process, laboratory verification was carried out and obtained moisture content of 0.77%, fat content of 48.70% and solubility of 87.31%.